Effect of nozzle diameter on jet impingement cooling system - Dulfharah, Nizam Memth Ali (2009)
This research focused on the study about the effect of nozzle diameter on jet impingement cooling system. The impinging jet can be described as a phenomenon in which the fluid exiting from a nozzle or orifice hits a wall or solid surface usually at normal angle. Impinging air jets have been widely used in many industrial applications in order to achieve enhanced coefficients for convective heating, cooling or drying. A single air jet or arrays of air jets, impinging normally on a surface are an effective method to enhance heat and mass transfer. Engineering applications that widely use air jets include cooling of hot steel plates, tempering of glass plates, drying of textiles and paper, cooling of turbine blades, electronic components and de-icing of aircraft. Experiments were conducted to determine the effect of nozzle diameter on the heat transfer coefficients from a small heat source to a jet impingement cooling system, submerged and confined air. The experiment were carried out with a single jet with three different nozzle diameter, d; 0.5, 1.0, 2.0 cm and four dimensionless jet to heat source spacing, S/d (6, 8, 10, 12) were tested within the laminar jet Reynolds number ranging from 500-2300. The results indicate that the heat transfer coefficient, h increase with the increasing nozzle diameter at the stagnation point region corresponding to 0< r/d <4. This may be attributed to an increase in the jet momentum and turbulence intensity level with the larger nozzle diameter, which results in the heat transfer augmentation. However, the effect of the nozzle diameter on the Nusselt numbers does not exist at the wall jet region corresponding to r/d>4. This may be attributed to the fact that the impinging jet flow characteristics are almost lost in the process of the re-development of the boundary layer after the jet impinges on the plate. By the increasing of the heat transfer coefficient, h the local Nusselt number, Nu also will be increase. This research are significant to improve the overheat component and devices problem nowadays. The results can also significantly increase the performance of the needed component in order to improve product reliability and customer satisfactions.